Is the Iliopsoas a Femoral Head Stabilizer? A Systematic Review - Takashi Hirase, M.D., M.P.H; Jason Mallett, B.S; Lindsay E. Barter, M.S; David Dong, B.S; Patrick C. McCulloch, M.D; Joshua D. Harris, M.D (Elsevier, 2020)
Purpose: To perform a systematic review of biomechanical and clinical studies to determine whether the iliopsoas is a femoral head stabilizer. Methods: A systematic review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Inclusion criteria were any human clinical (Levels I-IV evidence) or laboratory studies that investigated the role of the iliopsoas as a stabilizer of the hip. Exclusion criteria included studies that investigated patients undergoing spine surgery or those with a total hip arthroplasty or hip hemiarthroplasty. Study methodologic quality for clinical-outcomes studies were analyzed using the Modified Coleman Methodology Score. Because of the heterogeneity in the participants and interventions, no quantitative assimilative meta-analysis was performed. Results: Eight articles were analyzed (3 biomechanical [35 cadavers and 18 healthy subjects]; 5 clinical outcomes studies [537 subjects, 207 arthroscopic iliopsoas tenotomies]). Two in vivo biomechanical studies identified the iliopsoas as an anterior hip stabilizer. One cadaveric study identified the iliopsoas as a femoral head stabilizer at 0o-15o of hip flexion. Two clinical studies demonstrated the role of the iliopsoas as a dynamic hip stabilizer, particularly in patients with increased femoral version (greater than 15˚-25˚). Two studies reported cases of atraumatic anterior hip dislocations after arthroscopic iliopsoas tenotomies. Conclusions: Evidence from biomechanical and clinical studies may suggest that the iliopsoas is a dynamic anterior femoral head stabilizer. Level of Evidence: Level IV, systematic review of Level III and IV plus biomechanical studies.